Undergraduate Students’ Perceptions on their Identity as Future EFL Teachers - Mbato, Concilianus Laos; Wijaya, Kristian Florensio (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
To be professional EFL teachers in the future, pre-service teachers should continuously construct their identities amid various obstacles and difficulties they confront in their working circumstances. This study attempted to investigate undergraduate students’ perceptions of their identity as future teachers. One research problem was proposed in this study namely: What are the factors influencing pre-service teachers to develop their teacher identity through Micro Teaching Class? This study applied qualitative method harnessing three research instruments i.e., classroom survey, students’ reflections on their future teaching vocation, and interview to gather the data from Micro Teaching Class of the English Education Study Program, Sanata Dharma University, Yogyakarta. The findings indicated that most pre-service EFL teachers studying in Micro Teaching Class were willing to nurture their identities as future educators as long as extensive supports given to them. Future researchers need to conduct more intensive studies on the relationship between agency and resilience influencing pre-service EFL teachers’ professional identity development.